2020
DOI: 10.1085/jgp.201912501
|View full text |Cite
|
Sign up to set email alerts
|

A lower affinity to cytosolic proteins reveals VDAC3 isoform-specific role in mitochondrial biology

Abstract: Voltage-dependent anion channel (VDAC) is the major pathway for the transport of ions and metabolites across the mitochondrial outer membrane. Among the three known mammalian VDAC isoforms, VDAC3 is the least characterized, but unique functional roles have been proposed in cellular and animal models. Yet, a high-sequence similarity between VDAC1 and VDAC3 is indicative of a similar pore-forming structure. Here, we conclusively show that VDAC3 forms stable, highly conductive voltage-gated channels that, much li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 84 publications
(190 reference statements)
2
54
0
Order By: Relevance
“…We did not evaluate VDAC3 in these experiments, because the import of NADH in the mitochondrial inter-membrane space is not possible when the porin 1 deficient yeast is complemented by VDAC3, but not by VDAC1 and VDAC2 54 . It has recently been reported that tubulin also blocks VDAC3 55 : the paper showed that even 85 nM of tubulin produced fewer blockage events in VDAC3 in comparison to those by 45 nM tubulin in VDAC1, indicating that VDAC3 is much less sensitive to tubulin than VDAC1. Using 50 nM tubulin we were able to fully inhibit BP-induced swelling, suggesting that there was no involvement of VDAC3.…”
Section: Discussionmentioning
confidence: 91%
“…We did not evaluate VDAC3 in these experiments, because the import of NADH in the mitochondrial inter-membrane space is not possible when the porin 1 deficient yeast is complemented by VDAC3, but not by VDAC1 and VDAC2 54 . It has recently been reported that tubulin also blocks VDAC3 55 : the paper showed that even 85 nM of tubulin produced fewer blockage events in VDAC3 in comparison to those by 45 nM tubulin in VDAC1, indicating that VDAC3 is much less sensitive to tubulin than VDAC1. Using 50 nM tubulin we were able to fully inhibit BP-induced swelling, suggesting that there was no involvement of VDAC3.…”
Section: Discussionmentioning
confidence: 91%
“…This protein is a key control point for the passage of ions and metabolites and thus, guarantees cell energy production. During evolution, more isoforms were raised in the eukaryotic organisms [ 2 ]: they were characterized on the basis of their functional traits, revealing very close permeability features [ 3 , 4 , 5 , 6 , 7 ]. In addition, experiments aimed to study their expression patterns in different tissues indicated very subtle differences and a quite ubiquitous presence in the tested tissues [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the distribution of VDAC isoforms is more or less ubiquitous in tissues but with a prevalence of VDAC1 isoform. Although the three VDAC genes codify proteins with apparently the same function, differences in their amino acid content, the mitochondrial outer membrane localization [ 9 ], the channel functionality and voltage dependence [ 6 , 7 ], and the contribution of the N-terminal portion to cell viability and survival [ 10 ], lead to the hypothesis of a more specialized role/function for each isoform in different biological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no current structures of mammalian VDAC2 and VDAC3, the high degree of sequence similarity enables the construction of reliable homology models showing a conserved 3D structure (Amodeo et al, 2014). All three VDAC isoforms form almost identical anion-selective and voltage-gated ion channels in vitro when reconstituted into planar lipid membranes (Maurya and Mahalakshmi, 2015;Queralt-Martin et al, 2020).…”
Section: Overview Of Vdac Basic Channel Propertiesmentioning
confidence: 99%